Spiritualitas Kepedulian Sosial Berbasis Multikulturalisme di Kalangan Pemuda Gereja Bukit Zaitun Kota Makassar - Omedetho Jermias, Emanuel; Rahman, Abdul; Nasuhan, Najamuddin (Mahesa Research Center, 2024)
This research aims to narrate and analyze the spirituality of social care carried out by the youth of GPIB Bukit Zaitun in Makassar City. The method used in this research is a qualitative research method with a phenomenological approach. Data was collected through observation and interviews. The results of the research show that the church as a religious institution and educational institution has succeeded in guiding young people to return to the basic values of Christianity, namely having love and caring for others as part of their devotion to God. This success was marked by the presence of GPIB Bukit Zaitun youth to provide assistance to economically marginalized parties, both on institutional and personal behalf. Social care on behalf of the institution is realized by means of fundraising, distribution of consumption, creative education with orphans, and distribution of fast breaking packages. Meanwhile, social care on behalf of individuals is realized by giving a certain amount of money to the poor, for example old newspaper sellers, scavengers, and giving school supplies to orphans. The social awareness action carried out by the youth of GPIB Bukit Zaitun is multicultural, in the sense that it does not differentiate between the target recipients of aid in terms of their religion.